CT enterography: Mannitol versus VoLumen. Issue 5 (28th July 2016) - Wong, Jessica; Moore, Helen; Roger, Mark; McKee, Chris
Abstract: Introduction: Several different neutral oral contrast agents have been trialled in magnetic resonance and CT enterography (CTE). In the Auckland region, Mannitol 2.5% and VoLumen are both used in CTE. This study compares the performance of these two neutral oral contrast agents in CTE. Methods: Computed tomography enterography data were collected from 25 consecutive studies that used either Mannitol or VoLumen in 2014. All images were reviewed by three radiologists blinded to the type of oral contrast. Each quadrant was assessed for maximum distension, proportion of bowel loops distended, presence of inhomogeneous content and bowel wall visibility. Assessment also included whether the contrast agent reached the caecum and an overall subjective quality assessment. Patients were invited to answer a questionnaire regarding tolerability of the preparations. Results: Mannitol achieves better wall visibility in the right upper quadrant, left upper quadrant and left lower quadrant ( P  < 0.01). Overall differences in study quality favours Mannitol ( P  < 0.01) with 48% of the Mannitol studies being considered excellent compared with 4% of the VoLumen studies. There was no difference in maximal distension or proportion of loops distended. Conclusion: Mannitol in CTE achieves studies of a better quality than and is a viable alternative to VoLumen.